People of Diverse Genders and/or Sexualities and Their Animal Companions: Experiences of Family Violence in a Binational Sample. (December 2018) - Riggs, Damien W.; Taylor, Nik; Signal, Tania; Fraser, Heather; Donovan, Catherine
A significant body of research in the field of human–animal studies has focused on animals who live alongside humans within the home, with such animals often considered family members. To date, however, this research has focused almost exclusively on the experiences of heterosexual cisgender people, overlooking other diverse genders and/or sexualities. This article seeks to address this gap by reporting on findings from a study of 503 people living in Australia or the United Kingdom. Specifically, the research sought to explore links between psychological distress, social support, family violence, and views about animal companions. Notable among the findings was an interaction between having experienced familial violence and living with an animal companion, and the impact of both on psychological distress and social support. The article concludes by considering the implications of the findings for better understanding the lives of people of diverse genders and/or sexualities.